131I activity quantification of gamma camera planar images. (10th January 2017) - Barquero, Raquel; Garcia, Hugo P; Incio, Monica G; Minguez, Pablo; Cardenas, Alexander; Martínez, Daniel; Lassmann, Michael
Abstract: A procedure to estimate the activity in target tissues in patients during the therapeutic administration of 131 I radiopharmaceutical treatment for thyroid conditions (hyperthyroidism and differentiated thyroid cancer) using a gamma camera (GC) with a high energy (HE) collimator, is proposed. Planar images are acquired for lesions of different sizes r, and at different distances d, in two HE GC systems. Defining a region of interest (ROI) on the image of size r, total counts n g are measured. Sensitivity S (cps MBq −1 ) in each acquisition is estimated as the product of the geometric G and the intrinsic efficiency η 0 . The mean fluence of 364 keV photons arriving at the ROI per disintegration G, is calculated with the MCNPX code, simulating the entire GC and the HE collimator. Intrinsic efficiency η 0 is estimated from a calibration measurement of a plane reference source of 131 I in air. Values of G and S for two GC systems—Philips Skylight and Siemens e-cam—are calculated. The total range of possible sensitivity values in thyroidal imaging in the e-cam and skylight GC measure from 7 cps MBq −1 to 35 cps MBq −1, and from 6 cps MBq −1 to 29 cps MBq −1, respectively. These sensitivity values have been verified with the SIMIND code, with good agreement between them. The results have been validated with experimental measurements in air, and in a medium with scatter and attenuation. The counts in the ROI can be produced by direct, scatter and penetration photons. The fluence value for direct photons is constant for any r and d values, but scatter and penetration photons show different values related to specific r and d values, resulting in the large sensitivity differences found. The sensitivity in thyroidal GC planar imaging is strongly dependent on uptake size, and distance from the GC. An individual value for the acquisition sensitivity of each lesion can significantly alleviate the level of uncertainty in the measurement of thyroid uptake activity for each patient.